Development of Character Education-Based Modules on Environmental Pollution Material to Improve Environmental Care Attitudes - Izra Aulia Almi Harahap; Indayana Febriani Tanjung (Fakultas Keguruan dan Ilmu Pendidikan Universitas Labuhanbatu, 2023)
Character is defined as an individual driving engine to carry out an action, respond and respond to something. So that the most important thing instilled by a human being from an early age is character values through character education at school age. This study aims to develop a character education-based environmental pollution module. The research method used is 4D (Define, Design, Development, Dissamination). This research was conducted on class X students of MAN Asahan. The results showed that the assessment of the validation test of the material obtained was 88% (Valid), the assessment of the validation test of learning media experts was 89% (Valid), the assessment of character education experts was 80% (Valid), the response assessment by biology teachers was 95% (Very Practical), the average student response rating is 90% (Very Practical). Based on that it was concluded that the character education-based environmental pollution module that was developed was valid, practical and effective